The carbon catabolite repressor CreA is an essential virulence factor of Metarhizium acridum against Locusta migratoria. Issue 8 (22nd June 2022) - Song, Dongxu; Jin, Yumei; Shi, Youhui; Xia, Yuxian; Peng, Guoxiong
Abstract: BACKGROUND: CreA has been proved to be a core gene in asexual conidiation in Metarhizium acridum, which regulates the shift of normal conidiation and microcycle conidiation. At present, research on CreA in fungi has focused on carbon source metabolism. There is a lack of research on the effect of CreA in virulence of pathogenic fungi. RESULTS: The virulence of the MaCreA disrupted strain (Δ MaCreA ) for Locusta migratoria was lost by topical inoculation bioassay. The formation rate and turgor pressure of the appressoria decreased. Growth of Δ MaCreA in host hemolymph was delayed, and the number of hyphal bodies was significantly reduced. The conidial cell wall of Δ MaCreA became thicker, the mannan content decreased, and the chitin content increased significantly, and it was more sensitive to calcofluor white and Congo Red. α‐1, 3‐Glucan and β‐1, 3‐glucan are more exposed on the surface of Δ MaCreA conidia than on the wild type. Lmspätzle and Lmcactus, the immune response genes in the host Toll pathway, showed stronger transcriptional activities at the early stage of Δ MaCreA invasion. The phenoloxidase activity assay also showed stronger immunostimulation by Δ MaCreA in vitro . CONCLUSION: The main reasons for the loss of virulence of Δ MaCreA in the topical inoculation were the reduced penetration ability of appressoria, limited growth in hemolymph and stronger insect immunostimulation of Δ MaCreA . © 2022 Society of Chemical Industry. Abstract : The virulence of the MaCreA disrupted strain (Δ MaCreA ) for Locusta migratoria was lost by topical inoculation bioassay. No conidia were produced on the surface of the cadavers killed by Δ MaCreA, which means that the Δ MaCreA hyphal bodies will eventually be cleared by locusts.